2021
DOI: 10.1007/s00586-021-06891-4
|View full text |Cite
|
Sign up to set email alerts
|

The association between pain scores and disc height change following discectomy surgery in lumbar disc herniation patients: a systematic review and meta-analysis

Abstract: Purpose To evaluate the impact of discectomy on disc height (DH) in lumbar disc herniation (LDH) patients following discectomy surgery and address the association of DH change with pain score change. Methods We searched three online databases for randomized controlled trials (RCTs) and observational studies. In LDH patients, eligible for discectomy surgery, the changes in pre-and post-operative back and/or leg pain score and DH and/or disc height index (DHI) were considered as primary outcomes. Standardize mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“… 49 The average IH decreases by 11.2% within the first 12-month post operation, and further decreases by 16.6% by the 60-month follow-up post operation. 49 , 50 A smaller IHI represents a greater possibility of postoperative neuro-foramen and spinal canal stenosis. This may affect the postoperative VAS pain and ODI disability scores, thereby, affecting the overall quality of life of patients.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“… 49 The average IH decreases by 11.2% within the first 12-month post operation, and further decreases by 16.6% by the 60-month follow-up post operation. 49 , 50 A smaller IHI represents a greater possibility of postoperative neuro-foramen and spinal canal stenosis. This may affect the postoperative VAS pain and ODI disability scores, thereby, affecting the overall quality of life of patients.…”
Section: Discussionmentioning
confidence: 89%
“…[46][47][48] It is generally accepted that, after discectomy, IH decreases over time. 49 The average IH decreases by 11.2% within the first 12-month post operation, and further decreases by 16.6% by the 60-month follow-up post operation. 49,50 A smaller IHI represents a greater possibility of postoperative neuro-foramen and spinal canal stenosis.…”
mentioning
confidence: 89%
“…Scion software (Scion Corp., Frederick, MD, USA) was used to interpret and analyze the digitalized radiographs. The disc height index (DHI) was used to present the average intervertebral disc height [29]. DHI was calculated by averaging the measurements of anterior (a), middle (b), and posterior (c) parts of the intervertebral disc height.…”
Section: X-ray Assessmentmentioning
confidence: 99%
“…Although several studies have focused on LDHtriggered pain [3][4][5], current treatments are not fully effective in controlling such neuropathic pain, notably because our understanding of the mechanisms that underlying the pain is incomplete [6]. Recent research has found that the degree of pain caused by LDH is not completely consistent with the actual situation shown on imaging [7], and several patients with lumbar disk herniation do not experience obvious pain sensation, or the site of pain is not the lesion segment.…”
Section: Introductionmentioning
confidence: 99%